ON THERMODYNAMIC MODELS FOR REAL SOLUTIONS - Shvarov Yu.V. (My University, 2007)
The thermodynamic consistency of modern models of nonideal aqueous solutions is evaluated. It was shown that the models of concentrated aqueous solutions used in current studies are thermodynamically incorrect. Criteria were proposed for the thermodynamic consistency of physicochemical models of the nonideality of real solutions. An example is given for the correct extension of the Debye-Hueckel equation.